Taxonomic, phylogenetic and ecological diversity of Niphargus (Amphipoda: Crustacea) in the Hölloch cave system (Switzerland). Issue 3 (4th May 2017) - FiŠer, Cene; Konec, Marjeta; Alther, Roman; Švara, Vid; Altermatt, Florian
Abstract : Groundwater belongs to the spatially most extensive, but least explored freshwater systems. On a global scale, the species richness of several subterranean invertebrate taxa parallels species richness found in surface waters, while on a local scale species richness hardly exceeds 20 species. This results in a high contribution of groundwater ecosystems to regional β- and γ-diversity, and to a smaller degree to α-diversity, and deserves focused attention. In general, more species are to be found in large cave systems. The second largest cave system in Europe is Hölloch in Switzerland. In this paper we revised the taxonomic, phylogenetic and ecological diversity of the amphipod community in the Hölloch cave system. While previous records listed five geographically widespread species of the genus Niphargus for this cave system, we could not confirm the presence of any of those species, but rather found three highly distinct species new to science. In this paper we describe Niphargus styx sp. nov., Niphargus murimali sp. nov., and Niphargus muotae sp. nov., and suggest that previous records from that cave were probably misidentifications. Although amphipod species richness in this cave system seems to be lower than previously thought in terms of absolute numbers, the cave retained its regional and international importance in terms of nature conservation for multiple reasons. First, all newly described species are probably endemic to this cave system. Second, they are phylogenetically distantly related and exhibit moderate to high phylogenetic diversity. Third, the species, as inferred from their functional morphology, are also ecologically highly divergent. Based on geographic distribution of their nearest relatives, we hypothesize that the cave system was most likely independently colonized from North, West and South and that the pre-adapted ancestors occupied different ecological niches within the system. http://zoobank.org/urn:lsid:zoobank.org:pub:A19309E5-C06B-4844-A4D8-7571F05F25C9